2013
DOI: 10.2172/1111547
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion in Supercritical carbon Dioxide: Materials, Environmental Purity, Surface Treatments, and Flow Issues

Abstract: Executive SummaryThe supercritical CO 2 Brayton cycle is gaining importance for power conversion in the Generation IV Fast Reactor system because of its high power conversion efficiencies. When used in conjunction with a Sodium Fast Reactor for example, the supercritical CO 2 cycle offers additional safety advantages, by eliminating potential sodium-water interactions that may occur in a steam cycle. In power conversion systems for Generation IV Fast Reactors, supercritical CO 2 temperatures could be in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The carbon is likely due to diffusion after its release from CO 2 reaction with a metal as indicated in (R1) and (R2) or the Boudouard reaction (R3) of a CO buildup in the inner layer [12]. It can be hypothesized that carbide formation on the surface of the Ta and Nb samples prevented a completely continuous protective oxide scale from forming, leaving pathways for metal to diffuse out and form a nucleation point for further oxidation [20]. The dissolution of carbon into the underlying alloy at the grain boundaries could also cause a weakening of the bonds between the grains of the metal, which could lead to cracking or failure of the material [21].…”
Section: Discussionmentioning
confidence: 99%
“…The carbon is likely due to diffusion after its release from CO 2 reaction with a metal as indicated in (R1) and (R2) or the Boudouard reaction (R3) of a CO buildup in the inner layer [12]. It can be hypothesized that carbide formation on the surface of the Ta and Nb samples prevented a completely continuous protective oxide scale from forming, leaving pathways for metal to diffuse out and form a nucleation point for further oxidation [20]. The dissolution of carbon into the underlying alloy at the grain boundaries could also cause a weakening of the bonds between the grains of the metal, which could lead to cracking or failure of the material [21].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for each alloy at a given temperature, the increase in k p with increasing CO 2 pressure from 0.1 to 20 MPa was less than a factor of 2. Previously, Sridharan [27] reported that weight gains of Fe-rich oxide-forming Fe-based alloys (9-12 wt.% Cr) corroded in S-CO 2 at 450 • C (20 MPa) for 400 h were larger than those at 8.3 MPa, demonstrating the increase in the corrosion rate at higher CO 2 pressure. In addition, Pint and Keiser [14] recently reported the results of S-CO 2 corrosion tests for chromia-forming alloys at 650-750 • C for 500 h showing that weight gains in S-CO 2 (20 MPa) were larger than those in atmospheric CO 2 (0.1 MPa) with a similar degree of increase as observed in this study.…”
Section: Effect Of Co 2 Pressure On Corrosion and Carburization Kineticsmentioning
confidence: 96%
“…Desired material properties in these operating environments include exceptional static and dynamic strength, microstructural stability, and resistance to time‐dependent mechanisms such as creep and resistance to oxidation or interaction with thermal management system fluids such as supercritical carbon dioxide. [ 3 ] Of course, optimized convergence of these properties is demanding of the existing state‐of‐the‐art and of readily available metallic materials, providing momentum for substantial innovation in alloy development and design approaches to meet challenging needs for future energy and aircraft systems.…”
Section: Introductionmentioning
confidence: 99%
“…Desired material properties in these operating environments include exceptional static and dynamic strength, microstructural stability, and resistance to time-dependent mechanisms such as creep and resistance to oxidation or interaction with thermal management system fluids such as supercritical carbon dioxide. [3] Of course, optimized convergence of these properties is demanding of the existing state-of-the-art and of readily available metallic materials, providing momentum for substantial innovation in alloy development and design approaches to meet challenging needs for future energy and aircraft systems.A surge of alloy development has spawned from the field that originally retained the moniker of "high-entropy alloys". Complex concentrated alloys (CCAs) will be utilized in this account, whereby entropy is not of particular consideration, and the individual contribution of each element to the overall composition may be drastically altered in order to achieve a desired outcome.…”
mentioning
confidence: 99%